(untitled) (Balneo and PRM Research Journal, 2024)
Obesity has become a major public health problem due to its alarming increase in prevalence in recent years, both in children and adults. This medical condition is associated with increased morbidity and mortality rate, being the main risk factor for chronic diseases as type 2 diabetes, hypertension, cardiovascular diseases, dyslipidemia, non-alcoholic fatty liver disease and chronic kidney disease. Considering the fact that obesity is a multifactorial determined disease involving genetic, biological, behavioral and psychological factors, the approach to obesity should be performed in a multidisciplinary team. The management of obesity is complex and it includes non-pharmacological, pharmacological and, sometimes, surgical interventions. Nutrition interventions for obesity are focused not only on weight loss but also on long-term maintenance of the body weight achieved, including caloric restriction, macronutrient-based interventions, diatery fiber, meal replacements and intermittent fasting. For people living with obesity, the medical nutrition therapy shloud be in accordance with their individual values, preferences and treatment goals, in order to be maintained long term. In addition to diet, physical activity plays an important role in human health, contributing to the prevention of obesity and being part of its management, reducing metabolic risk factors and improving general condition.